STREET FOODS - A WAY OUT STRATAGEM TO ACHIEVE FOOD SECURITY AMONG LOW INCOME URBAN CLUSTERS - Chellappan, Sekar (Innovare Journal of Food Sciences, 2016)
Abstract Objective: A study was conducted to assess the consumer base of the street foods as well as the factors driving the consumption of street foods. Methods: For the purpose of primary survey, 250 consumers of street foods were chosen randomly at the rate of 125 each in Chennai and Coimbatore cities in Tamil Nadu State. Descriptive statistics were used to analyze the data. Results: Majority of the street food consumers (52.40 per cent) were mainly from Economically Weaker Section (EWS) with the annual average household income of Rs.82, 631. Women consumers of street food were comparatively low (only 31 per cent). Daily wage earners like construction workers, head loaders, cart pullers, hawkers and truck drivers About 60 per cent of the consumers had only temporary jobs. Consumers preferred the street food due to its inexpensiveness (40.40 per cent). About 57 per cent of the people enjoyed eating in the vending site itself. EWS and LIG consumers spent significantly (Rs.1032 and Rs.894, respectively) on traditional foods. It was understood that the cost of the street foods was about 45 to 50 per cent less when compared to local restaurants A vast majority of the consumers were either fairly satisfied (42.74 per cent) or satisfied (32.09 per cent) with the existing practices and the cuisine provided by vendors. Conclusion: The assessment showed that street food consumers were able to get the same level of nutrition as that of the consumers who dined in big restaurants or mess but at less cost. The results indicated that the absence of street food would have led to low intake of food by the consumers, whose purchasing power is low. Hence there is a need for strenuous efforts to improve the working environment, hygiene, food safety and the livelihood of street food vendors; so as to achieve and ensure food and nutritional security among the poor income clusters in the economy. Key Words: Street Food- Food Security – Consumers- Nutrition- Traditional Foods- Calorie-Livelihood.